Comparison of overweight and obese military‐dependent and civilian adolescent girls with loss‐of‐control eating. Issue 6 (8th May 2015) - Schvey, Natasha A.; Sbrocco, Tracy; Stephens, Mark; Bryant, Edny J.; Ress, Rachel; Spieker, Elena A.; Conforte, Allison; Bakalar, Jennifer L.; Pickworth, Courtney K.; Barmine, Marissa; Klein, David; Brady, Sheila M.; et al.
ABSTRACT Objective Limited data suggest that the children of U.S. service members may be at increased risk for disordered‐eating. To date, no study has directly compared adolescent military‐dependents to their civilian peers along measures of eating pathology and associated correlates. We, therefore, compared overweight and obese adolescent female military‐dependents to their civilian counterparts along measures of eating‐related pathology and psychosocial functioning. Method Adolescent females with a BMI between the 85th and 97th percentiles and who reported loss‐of‐control eating completed interview and questionnaire assessments of eating‐related and general psychopathology. Results Twenty‐three military‐dependents and 105 civilians participated. Controlling for age, race, and BMI‐z, military‐dependents reported significantly more binge episodes per month (p < 0.01), as well as greater eating‐concern, shape‐concern, and weight‐concern (p's < 0.01) than civilians. Military‐dependents also reported more severe depression (p < 0.05). Discussion Adolescent female military‐dependents may be particularly vulnerable to disordered‐eating compared with civilian peers. This potential vulnerability should be considered when assessing military‐dependents. © 2015 Wiley Periodicals, Inc. (Int J Eat Disord 2015; 48:790–794)